(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article initially provides an overview of the term parallelism and its usage in the field. It briefly outlines the types of syntactic parallelism—namely formal (structural) and semantic parallelism—while placing particular emphasis on the phenomenon of semantic parallelism. The study attempts to analyze the various forms of semantic parallelism using linguistic evidence.